Deep‐time convergent evolution in animal communication presented by shared adaptations for coping with noise in lizards and other animals. (30th June 2021) - Ord, Terry J.; Klomp, Danielle A.; Summers, Thomas C.; Diesmos, Arvin; Ahmad, Norhayati; Das, Indraneil
Abstract: Convergence in communication appears rare compared with other forms of adaptation. This is puzzling, given communication is acutely dependent on the environment and expected to converge in form when animals communicate in similar habitats. We uncover deep‐time convergence in territorial communication between two groups of tropical lizards separated by over 140 million years of evolution: the Southeast Asian Draco and Caribbean Anolis . These groups have repeatedly converged in multiple aspects of display along common environmental gradients. Robot playbacks to free‐ranging lizards confirmed that the most prominent convergence in display is adaptive, as it improves signal detection. We then provide evidence from a sample of the literature to further show that convergent adaptation among highly divergent animal groups is almost certainly widespread in nature. Signal evolution is therefore curbed towards the same set of adaptive solutions, especially when animals are challenged with the problem of communicating effectively in noisy environments. Abstract : We uncover adaptive convergences in multiple aspects of the territorial displays between two iconic lizard groups—the Southeast Asian Draco and the Caribbean Anolis —along common environment gradients. This convergence has occurred despite a separation of over 140 million years of evolution. We then compile new evidence from the literature to show that such deep‐time convergence is almost certainly widespread in nature. This paper reveals that deep‐time convergence is far more common than currently thought which refutes the superiority of history in shaping adaptive evolution in contemporary habitats while also highlighting the principal influence of the environment on signal evolution.